Effect of electroacupuncture on anxiety in patients with obesity: a protocol for a randomised, blinded, sham-controlled trial - Fan Zhang; Qing Yu; Qi Shu; Qiumei Peng; Wenxiu Duan; Rong-Lin Cai (BMJ Open)
Introduction Obesity is a growing public health issue worldwide, and anxiety is a major psychological disorder associated with obesity. Electroacupuncture (EA) has been proven to be a feasible treatment modality for obesity and anxiety in clinical practice. However, data on the effectiveness of EA for anxiety patients with obesity are lacking. Therefore, this study aimed to evaluate the effectiveness and safety of EA for anxiety in patients with obesity and to observe the brain functional status of the patients and the intervention effects of EA on brain function by using functional MRI (fMRI).Methods and analysis In this randomised, blinded, sham-controlled clinical trial, 72 patients with obesity from two hospitals with anxiety will be randomly divided into EA and control groups in a 1:1 ratio by using a random number table. Patients in the EA group will receive EA treatment with penetrating needling at specific acupoints for 8 weeks. The control group will receive Park’s acupuncture with non-penetrating needling. Weight, waist, body mass index, Self-rating Anxiety Scale score, State-Trait Anxiety Inventory score and Pittsburgh Sleep Quality Index will be measured before treatment, after 8 weeks of treatment and at the 1-month follow-up evaluation. Objective metabolic parameters such as triglyceride, total cholesterol, fasting blood glucose, ghrelin, leptin, cortisol and adrenocorticotropic hormone levels will also be measured before and after the 8-week intervention. 20 patients will be randomly selected from the EA and control groups before treatment. These randomly selected patients will undergo fMRI scans before and after treatment. Regional homogeneity, amplitude of low-frequency fluctuation and resting-state functional connectivity will be evaluated to compare the dysfunctional brain regions between two groups of patients after treatment.Ethics and dissemination The study protocol has been approved by the Hospital Ethics Committee of Second Affiliated Hospital of Anhui University of Chinese Medicine (2023-zj-42). Informed consent will be obtained prior to starting study-related procedures. The results will be disseminated in peer-reviewed journals and at scientific conferences.Trial registration number Chinese Clinical Trial Registry. ChiCTR2400083594, registered 29 April 2024.